The Crazy Machine: A PBL Approach in Third Year Embedded Systems Laboratories - Ortega-Sanchez, Cesar; Maynard, Clive (2014)
Engineers are first and foremost problem solvers. Industry is demanding graduating engineers to possess not only discipline knowledge, but also a complex set of professional skills that will allow them to contribute to the position from day one (Wagner, 2013). Demanded skills include, but are not limited to: ability to effectively work and communicate in interdisciplinary teams, life-long learning, disposition to embrace the company’s ethos and work ethics, problem-solving incorporating innovation, creativity and discipline rigour. To respond to this demand some universities are transforming the way engineering is taught (CDIO, 2013). This paper describes the laboratory work offered in two third-year units at the Electrical and Computer Engineering Department, Curtin University. The units involved are Embedded Software Engineering 302 (ESE 302) and Advanced Digital Design 320 (ADD 320). These units are taken by third year Computer, Mechatronic, Electronic and Telecommunication student engineers. Both units have separate lectures but share part of their laboratory work.